MODERN APPROACHES TO THE FORMATION OF INCLUSIVE EDUCATION COMPETENCIES IN OLIGOFRENOPEDAGOGUES - Madinakhon Arslanova (The Bioscan, 2024)
This article talks about the organizational and pedagogical aspects of the formation of inclusive competencies in future oligophrenopedagogues in the processes of education and society becoming more inclusive in higher education institutions.